Dispersion behaviors of Gaussian-type distribution of Curie temperature in relaxor ferroelectrics. Issue 4 (15th December 2015) - Cao, Wan Q.; Zhou, Chao; Pan, Rui K.; Qi, Ya J.
ABSTRACT: When the contributions of dipole and soften vibration mode are assigned to a complex impermeability and a real impermeability, respectively, the total complex permeability with frequency can be derived to modify the classical Landau-Devonshire theory. In a gaussian distribution and a skewed gaussian distribution of Curie temperature of second-order phase transition, the functions derived have the form of dispersion behavior of relaxor ferroelectrics. By comparing with experiment result, slight deviations appear on the two sides of peak of permittivity for the gaussian distribution, and improved by the skewed gaussian distribution. The relevant problems to be solved are proposed.